The Iconography of Divinity: Kali as a Power-Cluster of Ten Different Goddesses - Sapkota, Jiblal (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
This article is an exploration of Kali, a Hindu deity, through Panofskian three-tiered meanings of a visual art: pre-iconographical description, iconographical analysis and iconological interpretation. It presents neither a dogmatic nor an erotic interpretation of Kali but a purely objective analysis of the Hindu deity. It is argued that Kali has layers of implications, associations and meanings as well as multiple forms, namely Kali, Chinnamasta Kali, Tara, Bhuvaneshwori, Bagalamukhi, Dhumbavati, Kamala, Bhairavi, Sodasi, and Matangi. Each form is also associated with different mythologies, allegories and allusions of their origin. It is assumed that this article has had great significance in the academia as well as for the academicians and academics who are interested in carrying out research works, with an objective description, analysis and interpretation of any visual art. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10464 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 11-20